(untitled) (UUM Journal of Legal Studies, 2024)
In recent years, due to the COVID-19 pandemic, the world has suffered and undergone a radical transformation. At the beginning of 2020, the world was at the mercy of the COVID-19 pandemic. However, a ray of hope shone upon the world with the development of COVID-19 vaccination. Even though everyone needs to get vaccinated, it prompts a question about whether people can be forced to get vaccinated or if they should be able to choose for themselves. A welfare state must protect its citizens’ health. Despite this, citizens have reasons to be vaccinated against the virus. This paper discusses the abovementioned issue by analyzing judicial decisions, international legal instruments and contemporary data on pandemic situations. This study aimed to address the dilemma of mandatory vaccination and the independence of those who choose to vaccinate. The study revealed that a state can impose mandatory vaccination in certain situations, subject to legal and practical constraints. In contrast, individual freedom is always respected because human rights are vested in international and domestic law. While enforcing vaccination policies, an equitable balance between an authoritarian measure to protect public health and granting an exception to specific individuals, as well as honouring human rights, is the paramount approach.